Implementation of CPPB-IRT, WISE, and Halal Guarantee System on Bread Production - Suhardi, Bambang; Putri, Nabilla Indah; Astuti, Rahmaniyah Dwi (Jurnal Teknik Industri, 2019)
Bread is food that many consumed in Indonesia. It usually consumed and a substitute for rice. PT. X is an Indonesian company that produces dry bread and wet bread. The company must implement a Good Manufacturing Process (GMP) and Halal Guarantee System (HGS) to ensure the food safety that the company produced. The company is also obliged to pay attention to Occupational Safety and Health in the work environment by applying WISE. This study consists of five staged. The stages include identification of the condition of the company, CPPB inspection, WISE examination, HGS inspection, and proposed improvements in the production process. The results of the study show some elements that have not been fulfilled. These elements include 6 CPPB elements, 9 WISE elements, and 8 HGS elements. The results of the study also provided several studies. Some of the recipients were improvements in the Standart Operational Procedure (SOP) for the receipt and receipt of materials, and the SOP for the receipt and receipt of industrial non-processed materials.